STUDI FATWA PERBANKAN SYARIAH PADA AKAD MURABAHAH DI ERA KONTEMPORER - Azizah Mursyidah; Dewi purwati (JURNAL KAJIAN ISLAM MODERN, 2026)
This research aims to conduct a comprehensive study on the implementation of murabahah contracts in Indonesian Sharia banking and their compliance with DSN-MUI Fatwas in the contemporary era. The research methodology employs a qualitative descriptive analysis approach by integrating findings from academic journals and empirical studies published between 2000 and 2026. The results reveal that murabahah dominates the financing portfolio of Indonesian Sharia banking at 70-76%. Three implementation models were identified: Pure Murabahah (5%), Modified Ownership (20%), and Murabahah bil-Wakalah (75%), the latter being the most dominant yet a primary trigger for legal ambiguity and potential disguised riba. The Sharia compliance level shows that 65% of institutions are fully compliant, 25% are partially compliant, and 10% are non-compliant. Critical challenges identified include genuine ownership issues (89% of studies), margin transparency (76%), and overlapping wakalah-murabahah contracts (85%). The study recommends contract standardization, strengthening the role of Sharia Supervisory Boards (DPS), and integrating digital technologies like blockchain to enhance transparency and compliance. Keywords: Murabahah, DSN-MUI Fatwa, Islamic Banking, Sharia Compliance, Murabahah bil-wakalah.